Clinical impact of a pharmacist-led inpatient anticoagulation service: a review of the literature - Lee T; Davis E; Kielly J (Dove Medical Press, 2016)
Tiffany Lee, Erin Davis, Jason Kielly School of Pharmacy, Memorial University, St John's, NL, Canada Background: Anticoagulant therapies provide management options for potentially life-threatening thromboembolic conditions. They also carry significant safety risks, requiring careful consideration of medication dose, close monitoring, and follow-up. Inpatients are particularly at risk, considering the widespread use of anticoagulants in hospitals. This has prompted the introduction of safety goals for anticoagulants in Canada and the USA, which recommend increased pharmacist involvement to reduce patient harm. The goal of this review is to evaluate the efficacy and safety of pharmacist-led inpatient anticoagulation services compared to usual or physician-managed care. Methods: This narrative review includes articles identified through a literature search of PubMed, Embase, and International Pharmaceutical Abstracts databases, as well as hand searches of the references of relevant articles. Full publications of pharmacist-managed inpatient anticoagulation services were eligible if they were published in English and assessed clinical outcomes. Results: Twenty-six studies were included and further divided into two categories: 1) autonomous pharmacist-managed anticoagulation programs (PMAPs) and 2) pharmacist recommendation. Pharmacist management of heparin and warfarin appears to result in improvements in some surrogate outcomes (international normalized ratio [INR] stability and time in INR goal range), while results for others are mixed (time to therapeutic INR, length of stay, and activated partial thromboplastin time [aPTT] measures). There is also some indication that PMAPs may be associated with reduced patient mortality. When direct thrombin inhibitors are managed by pharmacists, there seems to be a shorter time to therapeutic aPTT and a greater percentage of time in the therapeutic range, as well as a decrease in the frequency of medication errors. Pharmacist recommendation services have generally resulted in a greater time in therapeutic INR range, greater INR stability, decreased length of stay, and reduced major drug interactions, with no significant differences in safety outcomes. Conclusion: Pharmacist-led inpatient anticoagulation management seems to result in superior outcomes, as compared to usual or physician-managed care. This conclusion is limited by small, poorly designed studies lacking statistical power, focusing mainly on surrogate outcomes. Keywords: hospital, clinical pharmacy, direct thrombin inhibitors, venous thromboembolism, warfarin, heparin